The inhibitory effects of vanillin on the growth of melanoma by reducing nuclear factor-κB activation - Marjan Pourhadi; Ahmad Ghasemi; Reza Abediny; Shaghayegh Haghjooy Javanmard; Golnaz Vaseghi (Advanced Biomedical Research, 2022)
Background: Melanoma is skin cancer, and the treatments are not efficient enough. Therefore, finding new drugs seems to be an essential need. Vanillin, which is extracted from vanilla seed, has anti-cancer effects by reducing nuclear factor-κB (NF). We explored the anti-tumor effects of vanillin in the melanoma model and its possible mechanism. Materials and Methods: In the MTT assay, mice melanoma cells (B16F10) were treated with vanillin (1, 2, 3, 4, 5 μg/mL) for 24 and 48 h. In an animal model, B16F10 was subcutaneously injected into C57BL/6 mice. After the development of tumors, the mice were treated with 50 and 100 mg/kg/day of vanillin for 10 days. The tumor size and expression level of NF-κB protein were measured. Results: In the MTT assay, vanillin in all concentrations significantly decreased B16F10 cell viability after 24 h incubation. The size of melanoma tumors was reduced in both doses 50 and 100 mg/kg/day in mice. NF-κB protein expression was decreased in the 100 mg/kg/day group in comparison with the control group. Conclusion: We found that vanillin by reducing NF-κB expression may have anti-tumor effects and reduced melanoma tumor size and cell viability.